2016
DOI: 10.1080/15299732.2016.1141150
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the efficacy and safety of prazosin versus placebo for the treatment of nightmares and sleep disturbances in adults with posttraumatic stress disorder

Abstract: PTSD-related nightmares, sleep disturbances, and overall illness severity showed a significant response to treatment with prazosin. With careful dose titration, prazosin was well tolerated and had no significant sustained effect on blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 21 publications
2
43
0
1
Order By: Relevance
“…21 This hypothesis led to clinical trials with adrenergic blockers (eg, clonidine and prazosin) that ultimately were not shown to be effective, although recent research has found prazosin to be effective for treating trauma-related nightmares, in part through its α-1 antagonist properties in normalizing sleep. 22 The most common HPA dysregulation finding included enhanced cortisol suppression following low-dose dexamethasone treatment. 23,24 These data suggested enhanced sensitivity to glucocorticoid activation.…”
Section: Theme 2: Dysregulated Circuitsmentioning
confidence: 99%
“…21 This hypothesis led to clinical trials with adrenergic blockers (eg, clonidine and prazosin) that ultimately were not shown to be effective, although recent research has found prazosin to be effective for treating trauma-related nightmares, in part through its α-1 antagonist properties in normalizing sleep. 22 The most common HPA dysregulation finding included enhanced cortisol suppression following low-dose dexamethasone treatment. 23,24 These data suggested enhanced sensitivity to glucocorticoid activation.…”
Section: Theme 2: Dysregulated Circuitsmentioning
confidence: 99%
“…In humans, the therapeutic dose of prazosin ranges from 3-20 mg per day (George et al 2016; Singh et al 2016). To determine the dose response range of prazosin in facilitating extinction, IP injections of 0.1, 0.5, or 2 mg/kg prazosin or vehicle (10% DMSO) were administered 1 hour prior to fear conditioning (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date most investigations of noradrenaline in fear conditioning have focused on limbic system β-ARs, which recruit intracellular Gs signaling and are required for fear memory acquisition (Bush et al 2010; Grillon et al 2004). However, interest in Gq-coupled α1-ARs has gained momentum since the selective α1-AR antagonist prazosin began to show promise in alleviating recurrent nightmares and other symptoms of PTSD (George et al 2016; Singh et al 2016). Despite the increasing prevalence of prazosin therapy in this condition, little is known about the role of α1-ARs in fear memory regulation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the low profile of side effects and the ability to improve sleep and reduce the nightmares after trauma prazosin has been recommended as an adjuvant therapy [7,8].…”
Section: Introductionmentioning
confidence: 99%